Association Between Inflammatory Bowel Disease and Erectile Dysfunction: A Nationwide Population-Based Study. Issue 5 (10th February 2016) - Kao, Chien-Chang; Lin, Cheng-Li; Huang, Wen-Yen; Cha, Tai-Lung; Lin, Te-Yu; Shen, Chih-Hao; Kao, Chia-Hung
Abstract: Background: To determine whether inflammatory bowel disease (IBD) is associated with an increased risk of subsequent erectile dysfunction (ED). Methods: We identified 1845 patients who received a diagnosis with IBD between 2000 and 2011 from Taiwan's National Health Insurance Research Database. For the comparison cohort, we randomly extracted the data of 7380 patients matched by sex, age, and baseline year. Follow-up continued until the development of ED, withdrawal from the National Health Insurance program, or the end of 2011. The cumulative incidences and hazard ratios (HRs) for ED development were determined. Results: After 12 years of follow-up, subsequent ED incidence rates in the IBD and comparison cohorts were 2.23 and 1.29 per 10, 000 person-years, respectively (adjusted hazard ratio = 1.64; 95% confidence interval [CI], 1.07–2.52; P < 0.05). Compared with the non-IBD cohort without comorbidity, the risk of ED was higher in the IBD cohort with comorbidity (adjusted hazard ratio = 2.46, 95% CI, 1.32–4.58). Patients with ulcerative colitis were 2.27-fold more likely to develop ED than were patients without IBD (95% CI, 1.22–4.20). Compared with patients without IBD who were aged ≤49 years, patients with IBD aged ≥65 years were 3.36-fold more likely to develop ED (95% CI, 1.42–7.96). Conclusions: We found that the patients with IBD had a 1.64-fold higher risk of developing ED than did the comparison group. Physicians should be aware of the link to ED when assessing patients with IBD.